Musik Bambu Wiragawi: Representasi Komodifikasi Bambu dari Hasil Strukturasi di Tiga Locus - Komarudin, Komarudin; Ramlan, Lalan; Laras, Meiga Fristya; Wiresna, Asep Ganjar; Saepudin, Asep (Resital: Jurnal Seni Pertunjukan, 2021)
Wiragawi Bamboo Music: the Representation of Commodification of Bamboo from the Structural Results at Three Locus. The purpose of this study is to describe the results of the commodification of Wiragawi Bamboo Music as a Representation of Structuring in Three Locus, among others, in West Java Province, Yogyakarta Special Region (DIY), and East Nusa Tenggara (NTT). This study uses a qualitative method with a deeper socio-cultural structuration, represented as a work in the form of commodification of bamboo as a musical instrument. The commodification of bamboo as a participatory of 'bamboo body grows' can legitimize an identity and regional authenticity as a form of cultural resilience based on a cultural economy. Bamboo plays an essential role in the cultural process, from birth to death according to its era, so it can be said that bamboo and humans have a close correlation, according to the locus of the area. Research findings include producing a set of Wiragawi bamboo musical instruments as a result of the commodification of bamboo music at three locuses, namely West Java Province, Yogyakarta Special Region (DIY), and East Nusa Tenggara (NTT). The conclusion shows that the primary material of bamboo is still very open to being a source of inspiration in creativity, mainly to produce various new instruments according to the interests and developments of the era.